Amido-bridged nucleic acids with small hydrophobic residues enhance hepatic tropism of antisense oligonucleotides in vivo1. Issue 12 (28th March 2015) - Yamamoto, Tsuyoshi; Yahara, Aiko; Waki, Reiko; Yasuhara, Hidenori; Wada, Fumito; Harada-Shiba, Mariko; Obika, Satoshi
<x xml:space="preserve">Abstract</x> High scalability of a novel bicyclic nucleoside building block, amido-bridged nucleic acid (AmNA), to diversify pharmacokinetic properties of therapeutic antisense oligonucleotides is described.